Representasi Liberalisme dalam Film Gran Turismo (Analisis Semiotika John Fiske) - Prasetyo, Diky Rizky; Nanda, Ertika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The research aims to understand how the representation of struggle is depicted through the journey faced by the main character in the film Gran Turismo. This research employs a qualitative method with a descriptive approach, as well as a semiotic analysis method by John Fiske using his Three Codes of Television, which divides social codes into three levels: the level of reality, the level of representation, and the level of ideology. Data collection was conducted through non-participant observation, with documentation in the form of screen captures. The results of this research include analyses of the level of reality, the level of representation, and the level of ideology. The level of reality is derived from several aspects, including gesture codes, expression codes, conversation codes, and behavior codes. The analysis of the level of reality in this film shows that the character Jann is portrayed as having a focused and patient attitude when facing problems. The level of representation analyzes scenes through audiovisual elements such as camera techniques, lighting, editing, music, and sound. The analysis of the level of representation in this film highlights the importance of aspects that support the film's appearance, making it more engaging and effectively conveying its message. The level of ideology analyzes the story presented in the film to determine the ideological concepts contained within it. The analysis of the level of ideology in this film reveals that the struggles of the main character against the currents of simplicity to become a professional racer illustrate that the film conveys a liberalism ideology, where liberalism represents the concept of individual freedom, particularly to become what one desires.